2012
DOI: 10.1542/peds.2012-0144
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sudden Cardiac Arrest

Abstract: Pediatric sudden cardiac arrest (SCA), which can cause sudden cardiac death if not treated within minutes, has a profound effect on everyone: children, parents, family members, communities, and health care providers. Preventing the tragedy of pediatric SCA, defined as the abrupt and unexpected loss of heart function, remains a concern to all. The goal of this statement is to increase the knowledge of pediatricians (including primary care providers and specialists) of the incidence of pediatric SCA, the spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 79 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…These 3 diseases would have most likely been able to be diagnosed by a pre-event EKG. The stimulant medication with prevalence of use in 2%–18% of the children in the general population [21], has central and peripheral catecholaminergic effects and has been documented in the literature as a possible contributor of acute mortality in children [3, 20, 2224]; however, one very large study has shown an elevated but statistically non-significant hazard ratio of SCA [25]. Stimulant use and abuse can lead to a statistically significant increase in heart rate [26, 27], blood pressure [26, 27] and cardiomyopathies, all increasing the risk for arrhythmias and sudden cardiac arrest [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These 3 diseases would have most likely been able to be diagnosed by a pre-event EKG. The stimulant medication with prevalence of use in 2%–18% of the children in the general population [21], has central and peripheral catecholaminergic effects and has been documented in the literature as a possible contributor of acute mortality in children [3, 20, 2224]; however, one very large study has shown an elevated but statistically non-significant hazard ratio of SCA [25]. Stimulant use and abuse can lead to a statistically significant increase in heart rate [26, 27], blood pressure [26, 27] and cardiomyopathies, all increasing the risk for arrhythmias and sudden cardiac arrest [24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent metanalysis has shown that an EKG has high sensitivity for mass screening in asymptomatic children with detectable causes of SCA such as hypertrophic cardiomyopathy, LQTS and WPW [29]. Current recommendations by American Academy of Pediatrics [3, 30, 31], FDA’s Pediatric Advisory Committee [32] and American Academy of Child and Adolescent Psychiatry [33] do not include an EKG for screening a child prior to starting stimulants for ADHD or participation in sports. The American Heart Association recommends that obtaining an EKG prior to starting the stimulants a reasonable option and further recommends a cardiology consult if there are any red-flags on history, physical examination or the EKG [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No screening protocol has yet proven to be effective in this role or validated as highly effective. 23) …”
Section: Discussionmentioning
confidence: 99%